Towards a culture-sensitive pedagogy of physics teacher education in Mozambique - Cupane, Alberto Felisberto (Curtin University, 2007)
The problem that I have found while looking for better ways of teaching physics science is that the curriculum we Mozambicans are using 30 years after independence can be hardly distinguished from the colonial curriculum. I generated my research questions based on this problem. I have adopted critical auto/ethnography and related trustworthiness criteria to respond to my research questions. I generated my data by looking from different perspectives at myself as learner, teacher and Mozambican citizen. This research suggests that the actual situation of largely reproducing a colonial science curriculum can be overcome by the inclusion of a view of the world that I call local-indigenous knowledge. I have achieved three main outcomes from this research: The transformation that occurred to me - One of the main transformations was to my perception of my cultural identity. Using contemporary theories of culture and rationality I have explored and more fully realised my Mozambican cultural identity. The meaning of indigeneity and local indigenous knowledge.This research has allowed me to reconceptualise the meaning of indigeneity by exposing how it has been applied in a discriminatory sense and how it could be applied to promote the human dimension that exists in all human beings. A cultural model of teaching - I propose the use of both local indigenous knowledge and World Modern Science to connect students to their history, their culture and their future. My cultural model of teaching encompasses four dimensions: (a) Use of local-indigenous language, (b) Learning by doing using locally available materials, (c) Use of stories to develop students' cultural awareness (identity) and (d) Inclusion of spirituality in science education. These outcomes, which can be deepened and/or transformed by future studies, can be seen as distant from my initial research goal of learning techniques to 'deliver well' the curriculum content of my physics classroom; but, for me, these outcomes illustrate the emergent characteristic of this qualitative inquiry into the self-culture dialectic.